A Comparison of the Quality of Informed Consent for Clinical Trials of an Experimental Hookworm Vaccine Conducted in Developed and Developing Countries. - David J Diemert; Lucas Lobato; Ashley Styczynski; Maria Zumer; Amanda Soares; Maria Flávia Gazzinelli (Public Library of Science (PLoS), 2017)
Informed consent is one of the principal ethical requirements of conducting clinical research, regardless of the study setting. Breaches in the quality of the informed consent process are frequently described in reference to clinical trials conducted in developing countries, due to low levels of formal education, a lack of familiarity with biomedical research, and limited access to health services in these countries. However, few studies have directly compared the quality of the informed consent process in developed and developing countries using the same tool and in similar clinical trials. This study was conducted to compare the quality of the informed consent process of a series of clinical trials of an investigational hookworm vaccine that were performed in Brazil and the United States. A standardized questionnaire was used to assess the ethical quality of the informed consent process in a series of Phase 1 clinical trials of the Na-GST-1/Alhydrogel hookworm vaccine that were conducted in healthy adults in Brazil and the United States. In Brazil, the trial was conducted at two sites, one in the hookworm non-endemic urban area of Belo Horizonte, Minas, and one in the rural, resource-limited town of Americaninhas, both in the state of Minas Gerais; the American trial was conducted in Washington, DC. A 32-question survey was administered after the informed consent document was signed at each of the three trial sites; it assessed participants' understanding of information about the study presented in the document as well as the voluntariness of their decision to participate. 105 participants completed the questionnaire: 63 in Americaninhas, 18 in Belo Horizonte, and 24 in Washington, DC. Overall knowledge about the trial was suboptimal: the mean number of correct answers to questions about study objectives, methods, duration, rights, and potential risks and benefits, was 45.6% in Americaninhas, 65.2% in Belo Horizonte, and 59.1% in Washington, DC. Although there was no difference in the rate of correct answers between participants in Belo Horizonte and Washington, DC, there was a significant gap between participants at these two locations compared to Americaninhas (p = 0.0002 and p = 0.0001, respectively), which had a lower percentage of correct answers. Attitudes towards participating in the clinical trial also differed by site: while approximately 40% had doubts about participating in Washington, DC and Belo Horizonte, only 1.5% had concerns in Americaninhas. Finally, in Belo Horizonte and Washington, high percentages cited a desire to help others as motivation for participating, whereas in Americaninhas, the most common reason for participating was personal interest (p = 0.001). Understanding of information about a Phase 1 clinical trial of an experimental hookworm vaccine following informed consent was suboptimal, regardless of study site. Although overall there were no differences in knowledge between Brazil and the US, a lower level of understanding about the trial was seen in participants at the rural, resource-limited Brazilian site. These findings demonstrate the need for educational interventions directed at potential clinical trial participants, both in developing and developed countries, in order to improve understanding of the informed consent document.